RARE-16. Differential expression of miRNAs in adamantinomatous craniopharynngioma reveals dysregulation of pathogenic pathways. (3rd June 2022) - Apps, John
Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate the expression of target mRNAs and can control whole gene networks. ACPs are benign pituitary tumours that can result in significant morbidity and premature mortality. ACPs harbour mutations in CTNNB1 and are driven by the activation of the WNT/beta-catenin pathway. We sought to explore the expression of miRNAS in adamantinomatous craniopharyngioma (ACP) in a cohort of samples previously subjected to RNA-Seq analysis (Apps et al, Acta Neuropathologica, 2018, May;135(5):757-777). Total RNA ACP samples (n=18), non-functioning pituitary adenomas (n=3) and normal foetal pituitaries (n=3) underwent miRNA sequencing using the Qiagen miRNA library prep kit on a NextSeq 500 to a depth of 16 million reads. Differential expression was performed using DESeq2 and functional analysis with mirPath v.3. Expression of miRNAs was correlated with previously published mRNA expression We found that 210 miRNA were upregulated and 275 down regulated in ACP compared with controls (adjusted p-value <0.1). MIR-205-5p was the most upregulated miRNA (619 fold) and its expression correlated with genes expressed within the tumour epithelium (e.g. TP63). miR-375 an inhibitor of the WNT pathway was the most down regulated miRNA (361 fold). KEGG Pathway analysis identified Glycosphingolipid synthesis as the most enriched pathway targeted by upregulated miRNAs. Pathways that were enriched by down regulated miRNAs included: ECM-receptor interaction, fatty acid biosynthesis, Hippo, TGF-beta, WNT, and ErbB pathways. Down regulation of miR-132 has previously been suggested as a marker of aggressiveness in ACP, and was 16 fold down regulated (adjusted p-value<0.001) in this cohort and expression was inversely correlated with genes relating to epithelial development. This data confirms previous studies indicating that miRNA expression is altered in ACP. In silico analysis suggest that the dysregulation of miRNA affects the expression of genes involved in pathogenic pathways in ACP.